Persepsi Terhadap Kualitas Pelayanan Pasien Asuransi Kesehatan Nasional Di Rumah Sakit Sitti Khadijah 1, Makassar - Ahmad Jayadie; Syamsuddin .; Muh. Erwin Rosyadi; Ruslan Agussalim; Thabran Talib (Institute Teknologi dan Kesehatan (ITEKES) Bali, 2025)
Abstract The focus of the research in this study is the perception of the quality of service of National Health Insurance patients in cesarean section at Sitti Khadijah 1 Hospital, Makassar. This study aims to determine the perception of the quality of service of National Health Insurance patients with cesarean section. The approach used in this study is a quantitative approach with a survey method. This study uses an applied research design. The resource in this study was based on accidental sampling of 31 cesarean section patients plus 3 staff from Sitti Khadijah 1 Makassar Hospital. The result of the study showed that Tangibles is in the quality category with a total percentage of 45.16%. and nonequality by 6.45%. The reliability dimension is in the quality category with a total percentage of 48.39%. and quite good at 35.48%. The responsiveness dimension is in the quality category with a total percentage of 38.71%. and quite quality of 35.48%. In the aspect of the assurance dimension, the score obtained in the quality category with a total percentage of 51.61%. However, there were still respondents who gave unqualified answers of 3.22%. In the aspect of the emphaty dimension, the score obtained in the quality category with a total percentage of 61.29%. and nonquality by 6.45%. Keywords: Quality of service, cesarean section patients, Sitti Khadijah 1 Makassar